Tax Misperception and Its Impact on Decision-Making: A Behavioral Response Model of Taxpayers - Faidul Adziem; Safri Haliding; Andi Nirma Baya Batara (Jurnal Riset Perpajakan: Amnesty, 2025)
Taxes are mandatory contributions imposed on individuals and business entities to finance public needs and maintain economic stability. One essential tax instrument in Indonesia is the Motor Vehicle Tax (Pajak Kendaraan Bermotor/PKB). However, misperceptions related to PKB continue to emerge among certain taxpayer groups. This study aims to: (1) analyze how misperceptions regarding motor vehicle taxes affect taxpayer decision-making related to PKB compliance in Makassar City, South Sulawesi; and (2) examine how misunderstandings of PKB regulations shape attitudinal and behavioral responses among taxpayers. This research employs a descriptive qualitative approach. Data were collected through interviews with SAMSAT officers in Gowa Regency and with taxpayers, including students from Muhammadiyah University of Makassar. Findings indicate that the general public does not exhibit substantial misperceptions about PKB, although potential misconceptions are more common among individuals aged 21–27 who pay taxes based on parental encouragement, and among women with limited experience in handling PKB obligations. Interviews with student respondents also revealed misperceptions driven by misinformation, misunderstanding of regulations, inadequate tax education, cognitive biases, framing, and demographic characteristics such as age, gender, and occupation. Overall, the study highlights that PKB-related misperceptions remain multidimensional and may influence taxpayer compliance behavior, underscoring the need for more targeted education and communication strategies.